Transition of Dislocation Structures in Severe Plastic Deformation and Its Effect on Dissolution in Dislocation Etchant - Muhammad Rifai; Ebad Bagherpour; Genki Yamamoto; Motohiro Yuasa; Hiroyuki Miyamoto (Advances in Materials Science and Engineering)
Transition of dislocation structures in ultrafine-grained copper processed by simple shear extrusion (SSE) and its effects on dissolution were manifested by simple immersion tests using a modified Livingston dislocation etchant, which attacks dislocations and grain boundaries selectively. The SSE process increased the internal strain evaluated by X-ray line broadening analysis until eight passes but decreased it with further extrusion until twelve passes. The weight loss in the immersion tests reflected the variation in the internal strain: namely, it increased until eight passes and then decreased with further extrusion to twelve passes. Taking our previous report on microstructural observation into account, it is suggested that variation in the internal strain is caused by both the variation in dislocation density and structural change of grain boundaries from equilibrium to nonequilibrium states or vice versa. Decreased dislocation density and structural change back to equilibrium state of grain boundaries in very high strain range by possibly dynamic recovery as pointed out by Dalla Torre were validated by X-ray and dissolution in the modified Livingston etchant in addition to the direct observation by TEM reported in our former report.